Pomposa, Comacchio, Ferrara: tabellioni and notaries (10th-12th centuries) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
The early medieval Ferrarese notariat is to date an unexplored field of research, due to the preservation of so many Ferrarese documents outside Ferrara and the few critical editions available. Starting from the work and the edition on the documents of the archive of Pomposa Abbey, the contribution aims to attempt some, initial reflections on the tabellioni and notaries of Ferrara between the 10th and 12th centuries. Within the universe of Ravenna's documentary practice, which remains proudly conservative until the beginning of the 13th century, the moves of the notaries of the Ferrarese area are shown to be more open to innovations and external influences. And the analysis of the charters and writers, which can be aggregated in the two areas around Ferrara and Comacchio, is conducted on titling, professional qualifications, facts of writing and ornamentation, in order to line up a few points and initiate the study of the Ferrarese notaries through the form and tenor of their charters.
Keywords: Notariat; 10th-12th centuries; Pomposa Abbey; Ferrara; medieval documents; writing